ENHANCING STUDENTS’ VISUALIZATIONABILITIES IN MOLECULAR PHYSICSLABORATORIES IN HIGHER EDUCATION VIA PEERTO-PEER (PEER INSTRUCTION) INTERACTIVEMETHOD - Khamidova Aziza Khayrullaevna (Euro Asian Journal Publishing, 2026)
This study investigates the effectiveness of the Peer-to-Peer (Peer Instruction) interactive methodology in enhancing students’ visualization abilities in molecular physics laboratory courses at higher education institutions. An experimental approach was employed involving two groups of undergraduate students: an experimental group exposed to peer instruction activities and a control group following traditional laboratory instruction. Pretest assessments indicated no significant difference between the groups, ensuring comparable baseline knowledge. Post-test results revealed that the experimental group demonstrated a substantial improvement in visualization skills, problem-solving, and conceptual understanding, with a mean increase of 28%, while the control group showed only a 9% improvement. Observational data and student interviews highlighted higher engagement, collaborative learning, and the ability to link theoretical concepts to practical laboratory applications in the experimental group. Statistical analysis confirmed the significance of these results at p < 0.05. The findings suggest that integrating peer instruction into molecular physics laboratories fosters not only visualization and conceptual understanding but also critical thinking, scientific reasoning, and cooperative skills, thereby providing empirical support for the implementation of student-centered interactive methodologies in higher education science curricula
Keywords: Molecular Physics; Peer Instruction